Contributions to a review of Philippine snakes, XIV The Snakes of the Genera Xenopeltis, Zaocys, Psammodynastes and Myersophis - Leviton, Alan E. (1983)
Four genera of snakes, three known from extra-Philippine localities in southeastern Asia, are treated in this report. These genera are not related to one another. They are considered together because they are small groups and can be handled conveniently at one time. The genus Xenopeltis belongs to the curious family Xenopeltidae, thought to be monotypic by most workers but to which others have assigned the equally odd Mexican genus Loxocemus. Underwoodl in his studies on the classification of snakes, concluded that the genus (and family)?... appears on the balance of characters to be a rather primitive and taxonomically rather isolated form.? Underwood places the family in the Infra-order Henophidiaalong with the families Aniilidae, Uropeltidae, Acrochordidae, and Boidae. These groups are not necessarily related, but they possess a number of supposedly primitive features1 not shared with other snakes. Smith's2 definition of the family and genus is followed here. In the Philippines Xenopeltis unicolor is known with certainty only from the Palawan Archipelago. It has been reported from other islands, but these records need confirmation. Elsewhere it has been reported from Borneo,Java, Sumatra, Malaya, and the whole of the Indo-Chinese region as far west as Burma and north into southern China. Zaocys and Psammodynastes are colubroid genera, the latter rearfanged and presumably mildly venomous, at least to small prey such as lizards, theformer non-venomous but because of its size and disposition able to inflict painful bites. These genera are found on islands of both eastern and western.